2014
DOI: 10.4238/2014.november.27.15
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of the Blumea balsamifera DC farnesyl diphosphate synthase gene

Abstract: ABSTRACT. Blumea balsamifera DC is a member of the Compositae family and is frequently used as traditional Chinese medicine. Blumea balsamifera is rich in monoterpenes, which possess a variety of pharmacological activities, such as antioxidant, anti-bacteria, and antiviral activities. Farnesyl diphosphate synthase (FPS) is a key enzyme in the biosynthetic pathway of terpenes, playing an important regulatory role in plant growth, such as resistance and secondary metabolism. Based on the conserved oligo amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Our results also showed that all of the dicotyledons were clustered into another group. This suggests that our analysis was accurate, as the results were similar to those of previous studies (Huang and Ke, 2014;Pang et al, 2014).…”
Section: Evolutionary Relationshipssupporting
confidence: 79%
“…Our results also showed that all of the dicotyledons were clustered into another group. This suggests that our analysis was accurate, as the results were similar to those of previous studies (Huang and Ke, 2014;Pang et al, 2014).…”
Section: Evolutionary Relationshipssupporting
confidence: 79%
“…Various experimental studies both in vitro and in vivo have reported the pharmacological activities of B. balsamifera, such as antioxidant, cytotoxic, antimicrobial, antifungal, anti-inflammatory, and hypolipidemic. Table-2 [13,22,56,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] summarizes some studies on the pharmacological activity of B. balsamifera.…”
Section: Progress On Pharmacological Studies Of B Balsamiferamentioning
confidence: 99%